An electrical analogy to Mie scattering - José M. Caridad (Nature Portfolio, 2016)
Until now experimental evidence of an electrical analogy to Mie scattering is lacking. Here, Caridad and Krstićet al. present an experimental demonstration of an electrical analogue to Mie scattering by using graphene as conductor, and circular potentials arranged in a canted two-dimensional array.